2008
DOI: 10.1186/1471-2458-8-34
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to colorectal cancer screening among ethnic minority groups in the UK

Abstract: Background: Colorectal screening by Flexible Sigmoidoscopy (FS) is under evaluation in the UK. Evidence from existing cancer screening programmes indicates lower participation among minority ethnic groups than the white-British population. To ensure equality of access, it is important to understand attitudes towards screening in all ethnic groups so that barriers to screening acceptance can be addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
67
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 29 publications
(26 reference statements)
8
67
1
Order By: Relevance
“…42,81 Our finding of low awareness of the purpose and value of bowel cancer screening across South Asian faith communities confirms previous findings. 42,55,73,75,81 A number of studies also found low knowledge and awareness of cancer and fearful perceptions of cancer in minority ethnic groups, 42,55,70,73,75,80,81 which mirrors our finding that awareness of cancer curability was perceived to be low across South Asian faith communities. Finally, we found perceived difficulties associated with the sampling and storage of faeces in order to complete the gFOBt kit, including limitations on getting help from family members owing to the personal nature of the test, which were also experienced within the majority (white European and African Caribbean) population.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…42,81 Our finding of low awareness of the purpose and value of bowel cancer screening across South Asian faith communities confirms previous findings. 42,55,73,75,81 A number of studies also found low knowledge and awareness of cancer and fearful perceptions of cancer in minority ethnic groups, 42,55,70,73,75,80,81 which mirrors our finding that awareness of cancer curability was perceived to be low across South Asian faith communities. Finally, we found perceived difficulties associated with the sampling and storage of faeces in order to complete the gFOBt kit, including limitations on getting help from family members owing to the personal nature of the test, which were also experienced within the majority (white European and African Caribbean) population.…”
Section: Discussionsupporting
confidence: 77%
“…42 Two studies exploring low uptake of bowel cancer screening by FS in diverse minority ethnic groups reported low knowledge and awareness of bowel cancer, anxiety about test invasiveness, fear of cancer, language difficulties, religious sensitivities and embarrassment as barriers to participation. 55,70 However, the relevance of these findings to low uptake of gFOBt is limited owing to differences in screening test procedures. Importantly, no studies have explored explanations for the differences in gFOBt uptake identified in the Muslim, Sikh and Hindu faith communities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding supports previous work reporting high levels of interest in FS screening and similar levels of intentions across the main UK ethnic groups. 34 In contrast, the data on uptake showed that these positive intentions were differentially translated into behaviour. Both Black and White respondents had significantly higher attendance rates than Asians (80% versus 69% versus 54%).…”
Section: Discussionmentioning
confidence: 68%
“…10 One study has specifically explored barriers to FS screening in UK ethnic minority groups, adding open-ended questions to a nationwide survey of the main ethnic minority groups, known as the Ethnibus Survey. 11 While there was high interest in screening, ethnic minority groups had lower levels of CRC awareness than white British adults and embarrassment was identified as a key barrier in the ethnic minority respondents. This study provided some suggestions about barriers to FS screening but was limited by the small number of questions and relatively few respondents were within the target age range for screening.…”
Section: Introductionmentioning
confidence: 99%